2014
DOI: 10.1039/c4cc05042h
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective [3+2] cycloaddition of N-tert-butanesulfinyl imines to arynes facilitated by a removable PhSO2CF2 group: synthesis and transformation of cyclic sulfoximines

Abstract: An unprecedented [3+2] cycloaddition between N-tert-butanesulfinyl imines and arynes provides a stereoselective method for the synthesis of cyclic sulfoximines. Not only does the difluoro(phenylsulfonyl)methyl group play an important role in facilitating the cycloaddition reaction, it can also be removed or substituted through the transformation of the difluorinated cyclic sulfoximines to cyclic sulfinamides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 51 publications
(6 reference statements)
1
26
0
1
Order By: Relevance
“…Thes ulfoximine 3e was isolated in 49 %y ield following the one-pot procedure compared to the 33 %o verall yield observed for the two-step method. [22] Furthermore,t he less reactive tert-butylsulfinimines (entries 3-7) were efficiently converted into the corresponding sulfoximines using this new protocol, although it was noted that these products were prone to thermal elimination of the tert-buyl group (this process was also noted by Hu and co-workers [13] in their cyclic sulfoximines). We also found that the method is compatible with less common sulfinimines such as biphenyl-or 3,5-bistrifluoromethylphenyl sulfinimine, which can be conveniently synthesised in one step from the parent aldehyde [14c] (entries 9a nd 10).…”
Section: Angewandte Chemiementioning
confidence: 78%
See 1 more Smart Citation
“…Thes ulfoximine 3e was isolated in 49 %y ield following the one-pot procedure compared to the 33 %o verall yield observed for the two-step method. [22] Furthermore,t he less reactive tert-butylsulfinimines (entries 3-7) were efficiently converted into the corresponding sulfoximines using this new protocol, although it was noted that these products were prone to thermal elimination of the tert-buyl group (this process was also noted by Hu and co-workers [13] in their cyclic sulfoximines). We also found that the method is compatible with less common sulfinimines such as biphenyl-or 3,5-bistrifluoromethylphenyl sulfinimine, which can be conveniently synthesised in one step from the parent aldehyde [14c] (entries 9a nd 10).…”
Section: Angewandte Chemiementioning
confidence: 78%
“…[12] Furthermore, they generally describe benzofused cyclic sulfoximines.T his limitation is found in the recent work reported by Hu et al where avery elegant one-step synthesis of cyclic sulfoximines was achieved, starting from enantiomerically pure sulfinimines,bycycloaddition with benzynes. [13] Herein we describe as imple and versatile method for the synthesis of nonfused six-membered cyclic sulfoximines with complete diastereocontrol and aw ide substrate range.…”
mentioning
confidence: 99%
“…Among sulfoximines, cyclic ones belong to an underutilized class of heterocycles, whose potential biological properties remain largely unexplored. Only a few methods including the 3+2 cycloaddition between N‐sulfinylimines and in situ generated benzynes and the sigmatropic rearrangement of N‐sulfinyl‐2‐vinylaziridines have so far been reported to produce cyclic sulfoximines from sulfinamide starting materials (Scheme b) . Very recently, Poisson et al.…”
Section: Figurementioning
confidence: 99%
“…The yield of 6 was improved to 66 % by using K 2 CO 3 as base at higher temperature. Cyclic sulfoximine ( R )‐ 3 a was converted to cyclic sulfinamide ( R )‐ 7 in good yield by treatment with HCl in methanol; however, this de‐ tert ‐butylation resulted in significant erosion of optical purity (Scheme c, Conditions A) . On the other hand, ( R )‐ 7 was obtained with high optical purity by treatment of ( R )‐ 3 a with BF 3 ⋅OEt 2 in the absence of water (Conditions B), and the present cyclization could be used for the asymmetric synthesis of cyclic sulfinamide.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation